THE TIME-SPACE CONTINUUM OF ACADEMIC ACHIEVEMENT: A CROSS-CULTURAL EXPLORATION OF TIME MANAGEMENT, MOTIVATION, AND STUDY ENVIRONMENT - Rayyan Cheong Tian Ming; Siti Nurhafizah Saleeza Ramlee; Liley Afzani Saidi; Nur Haffiza Rahaman; Wan Su Emi Yusnita Wan Yusof, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study explores the relationship between time management, motivation, and study environment practices and their impact on students' academic performance at the National Defense University of Malaysia (NDUM). Utilizing a quantitative research design, data were collected from 144 students enrolled in three major programs within the Defense Faculty of Research and Management. The structured questionnaire measured time management, motivation, and study environment practices using a five-point Likert scale. Pearson correlation analysis revealed significant positive correlations between academic performance and the variables of time management (r = .811, p < .001), motivation (r = .753, p < .001), and study environment (r = .617, p < .001). These findings underscore the critical roles of effective time management, sustained motivation, and a conducive study environment in enhancing academic outcomes. The study highlights the interdependent nature of these factors and suggests that targeted interventions addressing all three areas can significantly improve students' academic performance. However, the reliance on self-reported measures and the cross-sectional design present limitations, indicating the need for further longitudinal research to establish causal relationships.